1994
DOI: 10.1111/j.1468-0092.1994.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lateglacial Fauna From the Robin Hood Cave, Creswell Crags: A Re‐assessment

Abstract: Re-study of the fauna recovered in 1969 during excavations by John Campbell in front of the West Entrance to Robin Hood Cave, Creswell Crags, Derbyshire, England, shows it to include components of different ages. Arctic hare is the only species certainly exploited by humans and it is suggested that the position and character of cut-marks preserved on bone surfaces documents the processing and possible consumption of uncooked meat. It has not been possible to identify the time(s) of year when these hares died. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Artefacts and vertebrate remains, including Early Neolithic human bones, from these external sediments are of very different ages and it is suspected that part was derived from the cave's older internal deposits. However, all of the Late Upper Palaeolithic artefacts from this excavation are consistent with our definition of the Creswellian and radiocarbon dates on humanly modified bones of mountain hares (Lepus timidus) form a reasonably tightly constrained group (Charles and Jacobi, 1994). As no other Late Upper Palaeolithic technology appears to be represented it seems fair to associate the Creswellian artefacts and radiocarbon dates even though their depositional history is poorly understood.…”
Section: Reassessing the Chronology Of The British Late-glacialsupporting
confidence: 62%
“…Artefacts and vertebrate remains, including Early Neolithic human bones, from these external sediments are of very different ages and it is suspected that part was derived from the cave's older internal deposits. However, all of the Late Upper Palaeolithic artefacts from this excavation are consistent with our definition of the Creswellian and radiocarbon dates on humanly modified bones of mountain hares (Lepus timidus) form a reasonably tightly constrained group (Charles and Jacobi, 1994). As no other Late Upper Palaeolithic technology appears to be represented it seems fair to associate the Creswellian artefacts and radiocarbon dates even though their depositional history is poorly understood.…”
Section: Reassessing the Chronology Of The British Late-glacialsupporting
confidence: 62%
“…This bias can be caused by mastication of these bones during human consumption, as Landt (2004) recorded using data from Bofi in Central Africa, but could also be due to the presence of mammal carnivores, such as foxes, who commonly eat bones while consuming prey and then defecate elsewhere (Cochard, 2004a;Sanchis, 2010). Other authors observed differences in skeletal profiles based on the functionality of the site (Charles and Jacobi, 1994;García-Argüelles et al, 2004). For example, in localities where the skinning of lagomorphs as a regular activity, the anatomical representation consists mainly of distal appendicular elements, such as patellas and caudal vertebrae.…”
Section: Discussionmentioning
confidence: 94%
“…Several of the arctic hare bones have cut-marks and its importance to Creswellian hunters is shown by the number of bones from the caves at Creswell Crags (Charles & Jacobi 1994 Likewise, it is uncertain that all the species were locally present for the whole time during which the cave was used by Late Upper Palaeolithic humans. Several of the arctic hare bones have cut-marks and its importance to Creswellian hunters is shown by the number of bones from the caves at Creswell Crags (Charles & Jacobi 1994 Likewise, it is uncertain that all the species were locally present for the whole time during which the cave was used by Late Upper Palaeolithic humans.…”
Section: 480*130 Bpmentioning
confidence: 99%